Measuring the Dimensions of Success in Halal Food Business Sustainability: E-commerce Adoption, Halal Food Certificates, and Islamic Entrepreneurship Spirituality - Erike Anggraeni; Khavid Normasyhuri; Tri Atmaja Pramudita Wisnu Kusuma (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
The sustainability of the halal food business is faced with several crucial challenges. E-commerce adoption is a vital aspect that is often hampered by infrastructure limitations. Food certification is often hampered by complex bureaucratic processes that take a long time. Islamic entrepreneurial spirituality has not been deeply integrated into business practices. This study aims to examine the correlation between e-commerce adoption aspects, halal food certifications, and Islamic entrepreneurial spirituality in promoting the sustainability of the Halal Food Business in Lampung Province, Indonesia. The research methodology used in this research is quantitative, using SmartPLS 3.0 software. Primary data collection was carried out by taking a sample of respondents, namely Halal Food MSME business actors in Lampung Province, Indonesia, using a purposive sampling method. A total of 300 samples were used for this research. Data was obtained through the use of a Google Form, with indicator assessment carried out using a Likert scale. Research findings show that there is a relationship between the dimensions of e-commerce adoption, halal food certificates and Islamic entrepreneurial spirituality on the sustainability of halal food businesses in Lampung Province, Indonesia.